Ocean eddy momentum fluxes at the latitudes of the Gulf Stream and the Kuroshio extensions as revealed by satellite data - Greatbatch, R; Kohlmann, J; Czeschel, L; Zhai, X (2010)
Eddy momentum fluxes, i.e. Reynold stresses, are computed for the latitude bands of the Gulf Stream and Kuroshio extensions using 13 years of data from the merged satellite altimeter product of Le Traon et al. The spatial pattern and amplitude of the fluxes is remarkably similar to that found by Ducet and Le Traon using the 5 years of data that were available to them. In addition to updating the work of Ducet and Le Traon, we provide new insight into the role played by the underlying variable bottom topography, both for determining the structure of the eddy momentum fluxes seen in the satellite data and for influencing the way these fluxes feedback on the mean flow. While there is no clear evidence that eddies locally flux momentum into the eastward jets of the Gulf Stream and Kuroshio extensions, a clearer picture emerges after zonally integrating across each of the North Atlantic and North Pacific basins. We argue that the eddy momentum fluxes do indeed drive significant transport, a conclusion supported by preliminary results from a 3-D model calculation. We also present evidence that in the North Pacific, the Reynolds stresses are important for driving the recirculation gyres associated with the Kuroshio extension, taking advantage of new data from both observations and high-resolution model simulations. © 2010 Springer-Verlag.